ELORES: A NOVEL TREATMENT APPROACH IN ELECTRIC BURN PATIENT WITH BACTEREMIA AND VENTILATOR-ASSOCIATED PNEUMONIA: A CASE STUDY - Rupal, Sunny (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Rising challenge in treating nearly a million burn patients in India, with high mortality and morbidity attributed to nosocomial infections, is a serious concern. With cascades of reactions taking place in serious burn patients, there is a massive release of humoral factors, such as cytokines, prostaglandins, vasoactive prostanoids, and leukotrienes, along with multiple defects of cellular and humoral components of defense system. This immunocompromised state favors increased chances of nosocomial infections such as pneumonia and blood stream infections. The present case discusses a novel treatment approach with Elores (ceftriaxone, sulbactam, and adjuvant disodium edetate) in effectively treating burn patient with bacteremia and ventilator-associated pneumonia. Keywords: Bacteremia, Elores, Electric burns, Ventilator-associated pneumonia.